Management of Trigeminal Neuralgia with Botulinum Toxin Type A: Report of Two Cases - Craig Pearl; Brendan Moxley; Andrew Perry; Nagi Demian; Cyndie Dallaire-Giroux (MDPI AG, 2022)
Trigeminal neuralgia is a chronic pain condition associated with sharp, shock-like pain in one or more divisions of the trigeminal nerve. For patients who do not respond well to pharmacotherapy, there is growing evidence that Botulinum toxin type A injections into the trigeminal ganglion provide pain relief for several weeks up to several months at a time. One option is to administer injections into the trigeminal ganglion in Meckel's cave by inserting a needle through the Pterygopalatine Fossa using fluoroscopy to guide and confirm the proper needle placement. However, there is evidence that Botulinum toxin travels across nerve synapses; thus, injecting directly into the trigeminal ganglion may not be necessary. We present two patients with a confirmed diagnosis of trigeminal neuralgia who were treated by injecting Botulinum toxin type A intraorally into the mental foramen which resulted in 6 months or longer of pain relief. Injections into the mental foramen are much easier to administer than those administered directly into the trigeminal ganglion, and both patients treated with this technique experienced comparable results to what can be expected from traditional fluoroscopy-guided botulinum toxin injections. Though more research is needed, these cases potentially imply that a less-invasive injection may be sufficient in managing trigeminal neuralgia-related pain.